Peoples evaluation towards media facade as new urban landmarks at night - Moghaddam, Elyas Vahedi; Ibrahim, Rahinah (ArchNet-IJAR: International Journal of Architectural Research, 2016)
This paper attempts to help designers to turn a building into media facade as an attractive landmark for people’s urban night life. The literature survey points towards being dynamic and interactive with observers as the two quality dimensions for implementing this emerging lighting technology. Based on a survey of eleven selected media facades using video films to 250 students and staff at a public university, results identified twelve attributes for these two qualities. However, item analysis and exploratory factor analysis of the results determined only ten attributes actually support people’s attention towards media facade. The attributes of unique landmark, different nocturnal appearance, dynamic colour, informative lighting, artistic lighting performance, on going process, and dynamic advertisement could be categorized under the visual quality dimension. On the other hand, attributes of covert interaction, overt interaction, and predesigned interaction could be categorized under the interactive quality dimension. This study contributes in prioritizing visual qualities for guiding the attractiveness of buildings’ appearances at night, hence enabling the creation of new dynamic urban spaces when designing buildings.